The effects of racism and resilience on Black stroke- survivor quality of life: Study protocol and rationale for a mixed-methods approach - Love, Mary F.; Brooks, Andrea Nicole; Cox, Sonya D.; Okpala, Munachi; Cooksey, Gail; Cohen, Audrey Sarah; Sharrief, Anjail Z. (Frontiers in Neurology, 2022)
Introduction Stroke, a life-threatening stressor, often negatively impacts stroke-survivor (SS) quality of life (QoL). Annual age-adjusted incidence and death rates for stroke are significantly higher among Black Americans than among White Americans. Racism, a significant stressor, occurs at structural, cultural, and interpersonal levels and contributes to health disparities for Black SS. Resilience, a dynamic process of positive adaptation to significant stress, is impacted by factors or resources both internal and external to the individual. This study aims to examine the effects of experiences of racism and resilience on Black SS QoL during early stroke recovery. This article presents the study protocol. Methods and analyses This will be a prospective observational mixed-methods study. Black community-dwelling adults who are within 4 weeks of a stroke will be eligible for inclusion. Baseline measures will include the exposure variables of experiences of racism and resilience. Covariates measured at baseline include sociodemographic variables (age, sex, marital status, education, income, health insurance, employment status, number of people in household, residential address), clinical variables (date and type of stroke, inferred Modified Rankin Scale, anxiety and depression screening), and psychosocial variables (COVID-19 stress, perceived stress, mindfulness). The outcome variable (QoL) will be assessed 6-months post-stroke. Multiple-level linear regression models will be used to test the direct effects of experiences of racism, and the direct and indirect effects of resilience, on QoL. Qualitative data will be collected via focus groups and analyzed for themes of racism, resilience, and QoL. Discussion Racism can compound the stress exerted by stroke on Black SS. This study will occur during the COVID-19 pandemic and in the aftermath of calls for social justice for Black Americans. Experiences of racism will be measured with instruments for both “everyday” discrimination and vigilance. Sociodemographic variables will be operationalized to assess specific social determinants of health that intersect with structural racism. Because of the long-standing history of racism in the United States of America (USA), cultural influences and access to resources are central to the consideration of individual-level resilience in Black SS. Study results may inform the development of interventions to support Black SS QoL through enhanced resilience.